2021
DOI: 10.3390/lubricants9040036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Friction in Total Knee Prosthesis during a Standard Gait Cycle

Abstract: Total knee arthroplasty is on the rise worldwide. Despite its success, revision surgeries are also increasing. According to the American Joint Replacement Registry 2020, 3.3% of revision surgeries are due to wear, and 24.2% are due to mechanical loosening. The combination of shear stresses and wear particles occurring at the bone/implant interface can lead to local osteolysis. Although the shear stresses are partially driven by joint friction, relatively little is known about the evolution of the coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Their study examined the relationship between the coefficient of friction (CoF) during a gait cycle and its association with kinematics (slide-roll ratio), applied load, and relative velocity. As a result of this study, the coefficient of friction fluctuates with the change in load [12].…”
Section: Literature Reviewmentioning
confidence: 70%
“…Their study examined the relationship between the coefficient of friction (CoF) during a gait cycle and its association with kinematics (slide-roll ratio), applied load, and relative velocity. As a result of this study, the coefficient of friction fluctuates with the change in load [12].…”
Section: Literature Reviewmentioning
confidence: 70%
“…The results revealed that the value for the coefficient of friction for coated samples ranged between 0 and 0.15. It was also concluded that a decline in friction is due to an increase in load [104].…”
Section: Implant Failure: Friction and Wear Of Biomaterials Surfacementioning
confidence: 99%
“…One of the common causes of implant deterioration is reported as mechanical wear [105]. Knee implant failures result in 3.3% of modifying surgeries due to wear and 24.2% due to mechanical loosening [104]. Hip implants may result in osteolysis and the release of metal ions due to wear and corrosion of biomaterials [106].…”
Section: Implant Failure: Friction and Wear Of Biomaterials Surfacementioning
confidence: 99%
“…This is usually utilized in elderly patients to treat intracapsular hip fractures. , Bipolar hip hemiarthroplasty is made of 2 components: (1) a femoral stem with a small diameter and (2) a small diameter femoral stem together with a distinct acetabular component made of polyethylene (PE)-lined metal exterior. , Two elements of the bipolar hip implants join together as an articulating unit with the outermost diameter of the acetabular cap matching the acetabular width, while the internal surface of the acetabular cap articulates with the smaller head components for the femur. , Micromotion can occur between the femoral component and the acetabular and also at the articulation between the external surface of the acetabular component and the native joint tissue . Similarly, the THA is made of 2 components: (1) a stemmed femoral part with a femoral head and (2) an acetabular part. , For knee procedures, unicompartmental arthroplasty is frequently utilized for secluded unicompartmental arthritis, especially in the medial section in which a femoral condyle and the tibial articulation are resurfaced. , Total knee arthroplasty (TKA) procedures involve resurfacing the tibiofemoral surfaces and the articulation surfaces of the patella using bearing surfaces made of metal and PE materials. , …”
Section: Introductionmentioning
confidence: 99%
“…Under appropriate conditions, THA or TKA is deemed feasible for any patient after the age of bone maturity . Proper patient selection has yielded excellent results in 95% of patients. ,, The majority of recent hip replacement implants are made of modular systems, consisting of the femoral stem, femoral head, acetabular shell, and acetabular liner which are separate components. , Among the advantages of this newer system is that it allows greater flexibility in customizing, sizing, and fitting; however, it also comes with a disadvantage as components glide at the interfaces. …”
Section: Introductionmentioning
confidence: 99%